Nanoparticles: The efficacy of nanoparticle-based CT imaging techniques in identifying pro-inflammatory macrophages in atherosclerosis - Ahn, Matthew; Bansal, Suraj (The Meducator, 2022)
Atherosclerosis is an inflammatory condition characterized by severe arterial obstruction by the deposits of fatty plaques along the arterial walls. Pro-inflammatory macrophages contribute to the development of atherosclerotic plaques that underlie severe cardiovascular complications like myocardial infarction, making them an attractive diagnostic target. Given their high degree of selectivity, non-invasivity, and bioavailability, nanoparticles like N1177 and AuNP have recently entered the diagnostic landscape of atherosclerosis to improve tissue resolution in conventional imaging modalities like CT scans. Nevertheless, this approach has potential limitations of cytotoxicity and carcinogenic risks. Atherosclerosis accounts for one of the leading causes for morbidities worldwide which indicates an inherent need for equitable, accessible, and proactive diagnostic procedures. The purpose of this literature review is to evaluate macrophage-targeted nanotechnologies for in vivo diagnosis of atherosclerosis and their clinical potential. This literature review was conducted according to the PRISMA-S checklist through Ovid MEDLINE and Google Scholar